A4.17 Anti-citrullinated proteins antibodies promotes osteoclastogenesis and bone destruction in rheumatoid arthritis. (13th February 2015) - Krishnamurthy, A; Joshua, V; Wähämaa, H; Tarasova, N; Cerqueira, CF; Vivar, N; Engström, M; Amara, K; Malmström, V; Klareskog, L; Ytterberg, J; Catrina, AI
Abstract : Background/Purpose: Presence of ACPA is a major risk factor for bone erosion in RA and antibodies against modified citrullinated vimentin induce osteoclast (OC) formation from monocytes. We aimed to identify new molecular mechanisms responsible for ACPA-mediated bone destruction by investigating the direct effect of ACPA (obtained from the synovial fluid (SF) and peripheral blood (PB) of RA patients) on osteoclastogenesis and their influence on distinct osteoclasts precursors (monocytes/macrophages (MΦ) and immature dendritic cells (DC)). Methods: ACPA and non-ACPA IgGs were isolated from SF, (n = 26) and PB (n = 38) samples of RA patients. Osteoclasts precursors were generated (DC and MΦ) from ACPA + RA patient and healthy donors PB and then differentiated into OC in presence of RANKL and M-CSF. In parallel, cells were grown on osteoassay surfaces and bone resorption area was quantified. In-house generated monoclonal anti-citrulline antibodies cloned from SF B-cells were also tested. Cytokines were measured by cytometric bead array in culture supernatants. Mass spectrometry (MS) analysis was performed on different stages of OC maturation. Immunohistochemistry (IHC) was used to stain the OCs with biotinylated ACPA IgG and monoclonal anti-citrulline antibodies. The effect of PAD inhibition (Cl amidine) and IL-8 inhibition was tested in the cultures. Results: ACPAs pools enhanced osteoclastogenesis from both DC (fold change of (FC) 1.6 ± 0.14 for OC number) and MΦ (FC 2.0 ± 0.6 for OC and 1.6 ± 0.4 for bone resorption area (erosion)) of healthy donors. Similar effect was observed when the precursor cells were derived from ACPA + RA patients in both DC (FC 2.3 ± 0.9 OC and 2.6 ± 0.1 erosion) and MΦ (FC 1.8 ± 0.6 OC and 2.3 ± 0.7 erosion). Increased osteoclastogenesis was associated with significantly higher levels of IL-8 levels in culture supernatants measured at all stages of osteoclasts maturation from both DC (FC 2.4 ± 0.5) and MΦ (FC 2.0 ± 0.5). Interestingly SF levels of IL-8 were higher in ACPA + RA patients as compared to disease controls. IL-8 neutralisation completely abolished ACPAs effects while blocking PAD enzymes resulted in a complete inhibition of OC formation. MS analysis showed the presence of actin and vimentin citrullinated during osteoclastogenesis. Two of the tested anti-citrullinated monoclonal antibodies (D10 and B2) but not a third anti-citrulline antibody (C7) nor a negative anti-tetanus control antibody (E2) bound to osteoclasts and promoted osteoclastogenesis and bone destruction, interestingly Fab fragments of the D10 and B2 antibodies retained similar effects. Conclusion: In conclusion, SF and PB derived ACPA IgGs with broad specificities enhanced osteoclastogenesis from both DC and MΦ. This effect appears to be restricted to certain ACPAs specificities, IL-8 dependent and at least partially mediated through a Fab mediated mechanism.